MicroRNAs: protective regulators for neuron growth and development - Zhi-Xuan Ma; Zhen Liu; Hui-Hui Xiong; Zong-Pu Zhou; Li-Si Ouyang; Fu-Kang Xie; Ya-Mei Tang; Zhong-Dao Wu; Ying Feng (Neural Regeneration Research, 2023)
MicroRNAs (miRNAs) play an important regulatory role in neuronal growth and development. Different miRNAs target different genes to protect neurons in different ways, such as by avoiding apoptosis, preventing degeneration mediated by conditional mediators, preventing neuronal loss, weakening certain neurotoxic mechanisms, avoiding damage to neurons, and reducing inflammatory damage to them. The high expression of miRNAs in the brain has significantly facilitated their development as protective targets for therapy, including neuroprotection and neuronal recovery. miRNA is indispensable to the growth and development of neurons, and in turn, is beneficial for the development of the brain and checking the progression of various diseases of the nervous system. It can thus be used as an important therapeutic target for models of various diseases. This review provides an introduction to the protective effects of miRNA on neurons in case of different diseases or damage models, and then provides reference values and reflections on the relevant treatments for the benefit of future research in the area.